Oxygen atom transfer catalysis by dioxidomolybdenum(VI) complexes of pyridyl aminophenolate ligands - Hossain Md Kamal; Schachner Jörg A; Haukka Matti; Richmond Michael G; Mösch-Zanetti Nadia C; Lehtonen Ari; Nordlander Ebbe (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
A series of new cationic dioxidomolybdenum(VI) complexes [MoO2(L-n)]PF6 (2-5) with the tripodal tetradentate pyridyl aminophenolate ligands HL2-HL5 have been synthesized and characterized. Ligands HL2-HL4 carry substituents in the 4-position of the phenolate ring, viz. Cl, Br and NO2, respectively, whereas the ligand HL5, N-(2-hydroxy-3,5-di-tert-butylbenzyl)-N,N-bis(2-pyridylmethyl)amine, is a derivative of 3,5-di-tert-butylsalicylaldehyde. X-ray crystal structures of complexes 2, 3 and 5 reveal that they have a distorted octahedral geometry with the bonding parameters around the metal centres being practically similar. Stoichiometric oxygen atom transfer (OAT) properties of 5 with PPh3 were investigated using UV-Vis, P-31 NMR and mass spectrometry. In CH2Cl2 solution, a dimeric Mo(V) complex [(mu-O){MoO(L-5)}(2)](PF6)(2) 6 was formed while in methanol solution an air-sensitive Mo(IV) complex [MoO (OCH3)(L-5)] 7 was obtained. The solid-state structure of the mu-oxo bridged dimer 6 was determined by X-ray diffraction. Complex 7 is unstable under ambient conditions and capable of reducing DMSO, thus showing reactivity analogous to that of DMSO reductases. Similarly, the OAT reactions of complexes 2-4 also resulted in the formation of dimeric Mo(V) and unsaturated monomeric Mo(IV) complexes that are analogous to complexes 6 and 7. Catalytic OAT at 25 degrees C could also be observed, using complexes 1-5 as catalysts for oxidation of PPh3 in deuterated dimethylsulfoxide (DMSO d(6)), which functioned both as a solvent and oxidant. All complexes were also tested as catalysts for sulfoxidation of methyl-p-tolylsulfide and epoxidation of various alkene substrates with tert-butyl hydroperoxide (TBHP) as an oxidant. Complex 1 did not exhibit any sulfoxidation activity under the conditions used, while 2-5 catalyzed the sulfoxidation of methyl-p-tolylsulfide. Only complexes 2 and 3, with ligands containing halide substituents, exhibited good to moderate activity for epoxidation of all alkene substrates studied, and, in general, good activity for all molybdenum(VI) catalysts was only exhibited when cis-cyclooctene was used as a substrate. No complex catalysed epoxidation of cis-cyclooctene when an aqueous solution of H2O2 was used as potential oxidant. (C) 2021 The Authors. Published by Elsevier Ltd.